Effect Of Spiritual Leadership And Psychological Contracts On Employee Job Satisfaction At Indonesian Islamic Bank (BSI) Bandung Branch - Usep Suherman; Eeng Ahman; Disman Disman (Jurnal Manajerial, 2023)
Background - Job satisfaction is a happy emotional state or positive emotion that comes from evaluating one's work or experience. With high job satisfaction will increase employee performance against the organization where they work. Lack of satisfaction with the company can lead to low employee performance. In this study related to job satisfaction of BSI Bandung Branch employees. Aim - The aims of this study were to identify and analyze the influence of spiritual leadership and psychological contracts on employee job satisfaction at BSI Bandung Branch. Design / Methodology / Approach – This study used descriptive and explanatory survey methods. The research was conducted on 90 BSI employees. Sampling was carried out using a saturated sampling technique. The data analysis technique used is Multiple Regression Analysis. Findings – The results of this study show that spiritual leadership and psychological contracts partially or jointly have an impact on employee job satisfaction. Furthermore, a determinant value of 0.938 was obtained, this means that spiritual leadership and psychological contracts are able to explain employee job satisfaction of 93.8%. Meanwhile, 6.2% was caused by other factors. Conclusion - The leadership of the BSI Bandung Branch must be able to implement spiritual leadership for employees and build a strong psychological contract for employees within the company. Job satisfaction needs to be improved again to improve organizational performance. Research implication - To increase employee job satisfaction, it is necessary to pay attention to the attitudes and behavior of leadership shown by leaders to employees besides strengthening the psychological contract between employees and the organization. Limitation - The scope of this research is limited to one particular company, so it does not reflect the situation of other institutions in the same study regarding spiritual leadership, psychological contract, job satisfaction